Das urologische Dyna-CT - Michel, Maurice Stephan; Ritter, Manuel; Schönberg, Stefan; Häcker, Axel; Weisser, Gerald (Der Urologe, 2012)
BackgroundThe development of a new urological intervention table now enables the application of an Artis zee® ceiling Dyna-CT (Siemens, Erlangen, Germany) for interventional cross-sectional imaging and 3-D reconstruction of the urinary tract in the prone and supine positions (urological Dyna-CT).Materials and methodsWe tested the feasibility of the urological Dyna-CT with the newly developed urological intervention table. The system was moved five times to enable 3-D reconstruction of the urinary tract of a test person in the prone and in supine positions.ResultsHandling of the free floating table is easily possible during the intervention. We found no limitation of imaging system movement in any position of the test person.ConclusionApart from standard urological imaging such as fluoroscopy, intravenous pyelography or plain abdominal X-ray the urological Dyna-CT enables further imaging of the urinary tract. Fluoroscopy sequences can be stored as videos, and 3-D reconstructions of the urinary tract are possible with permanent patient access for any intervention. Extensive tests led to the technical approval of the system in urology.